Investigating communication in primary three Bruneian classroom - Khalid, Madihah (2008)
The emphasis on communication is more apparent in mathematics classrooms of recent years as open-ended teaching and teaching via problem solving become more popular. Communication is considered as one of the mathematical processes that need to be inculcated through the teaching of mathematical content in the Bruneian curriculum. The emphasis is stated in the current curriculum document. Communication is a way of sharing ideas and clarifying understanding. When children think, respond, discuss, elaborate, write, read, listen and inquire about mathematical concepts, they reap dual benefits: they communicate to learn mathematics and they learn to communicate mathematically. So how do children in Bruneian classrooms communicate? This report will investigate communication as children in Primary 3 learn about solids. Different representations were used by the teacher to make sure that she communicates meaning to the children to make them understand the topic.